Expression of the Tumor-associated Mucin 1 Epitope Analyzed with the Humanized PankoMab-GEX(TM) Antibody in Malignant and Normal Tissues of the Head and Neck - Wiest, Irmi; Alexiou, Christoph; Friese, Klaus; Betz, Peter; Tuebel, Jutta; Goletz, Steffen; Dian, Darius; Jeschke, Udo (Anticancer Research, 2016)
During neoplasia, glycosylation changes. In this setting, mucins, especially mucin 1 (MUC1), become carriers for oncofetal carbohydrates and relieve invasive growth. The recently described tumor-associated MUC1 epitope TA-MUC1 is primarily restricted to malignancies and is overexpressed in these tissues. The humanized monoclonal antibody PankoMab-GEX specifically recognizes TA-MUC1.Laryngeal cancer specimens (n=125) and normal tissue of head and neck (n=7) were used in this study. Paraffin-embedded sections were incubated with PankoMab-GEX. Staining reaction was carried out using peroxidase (POD) labeling and diaminobenzidine (DAB). Breast cancer tissue was used as positive control and negative control used non-specific mouse IgM. Semi-quantitative evaluation by two independent double-blinded investigators, including a pathologist, used the immunoreactive score (IRS) of Remmele and Stegner.A total of 31 out of 125 laryngeal cancer specimens were classified as G1. Of these, 22 (71%) were completely negative for TA-MUC1, the remaining 9 showed very weak staining, with an IRS of 2. A total of 94 cases of cancer specimens were classified as G2 and G3; 34 of them were also negative, but 60 had an IRS of up to 9. All investigated normal tissue of the upper aerodigestive tract was completely negative for TA-MUC1.G1 tumors are completely negative or do not reach an IRS relevant range. The finding that G1 tumors are completely negative for TA-MUC1 or have IRS<=2 can be helpful for histopathological examination, especially concerning tumor grading. Therefore, this antibody holds great potential for use as a therapeutic antibody in laryngeal cancer.
EVALuna2:9426

Low digit ratio (2D:4D) in male suicide victims - Lenz, Bernd; Thiem, Daniela; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Stoessel, Christina; Betz, Peter; Kornhuber, Johannes (Journal of Neural Transmission, 2016)
Although women attempt suicides equally or more often than men do, men are more likely to die of suicide than women (sex paradox of suicidal behavior). Furthermore, the male traits of aggression and impulsivity predict suicide completion. Here, we studied the second-to-fourth-finger length ratio (2D:4D), a proxy for prenatal androgen exposure, in 46 suicide corpses and 25 non-suicide corpses. We report significantly lower 2D:4D in male suicide corpses than non-suicide corpses (p = .030, partial ? (2) = .147). There was no significant association between 2D:4D and the suicide method. Our findings indicate increased risk of suicide following higher prenatal androgen exposure in males. The results may improve future efforts to predict and prevent suicides.
EVALuna2:9427

Renal tubular HIF-2α expression requires VHL inactivation and causes fibrosis and cysts - Schietke, Ruth E.; Hackenbeck, Thomas; Tran, Maxine; Guenther, Regina; Klanke, Bernd; Warnecke, Christina; Knaup, Karl X.; Shukla, Deepa; Rosenberger, Christian; Koesters, Robert; Bachmann, Sebastian; Betz, Peter; et al. (PLoS ONE, 2012)
The Hypoxia-inducible transcription Factor (HIF) represents an important adaptive mechanism under hypoxia, whereas sustained activation may also have deleterious effects. HIF activity is determined by the oxygen regulated α-subunits HIF-1α or HIF-2α. Both are regulated by oxygen dependent degradation, which is controlled by the tumor suppressor "von Hippel-Lindau" (VHL), the gatekeeper of renal tubular growth control. HIF appears to play a particular role for the kidney, where renal EPO production, organ preservation from ischemia-reperfusion injury and renal tumorigenesis are prominent examples. Whereas HIF-1α is inducible in physiological renal mouse, rat and human tubular epithelia, HIF-2α is never detected in these cells, in any species. In contrast, distinct early lesions of biallelic VHL inactivation in kidneys of the hereditary VHL syndrome show strong HIF-2α expression. Furthermore, knockout of VHL in the mouse tubular apparatus enables HIF-2α expression. Continuous transgenic expression of HIF-2α by the Ksp-Cadherin promotor leads to renal fibrosis and insufficiency, next to multiple renal cysts. In conclusion, VHL appears to specifically repress HIF-2α in renal epithelia. Unphysiological expression of HIF-2α in tubular epithelia has deleterious effects. Our data are compatible with dedifferentiation of renal epithelial cells by sustained HIF-2α expression. However, HIF-2α overexpression alone is insufficient to induce tumors. Thus, our data bear implications for renal tumorigenesis, epithelial differentiation and renal repair mechanisms. © 2012 Schietke et al.